2012
DOI: 10.1007/s11240-012-0243-5
|View full text |Cite|
|
Sign up to set email alerts
|

Primary and secondary somatic embryogenesis in Chrysanthemum cv. Euro

Abstract: Somatic embryogenesis was induced from in vivo grown leaf explants of Chrysanthemum cv. Euro incubated on Murashige and Skoog (MS) medium supplemented with 2.0 mg/L 2,4-dichlorophenoxyacetic acid and 2.0 mg/L Kinetin, yielding the highest mean number of embryos (42 ± 5.97) per explant after 5 weeks of culture. We evaluated the effects of basal medium, various concentrations of sucrose, and timentin on the proliferation of secondary somatic embryos. MS medium was observed to be the more effective in promoting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
1
20
1
1
Order By: Relevance
“…Here it could be noticed that the two different media (WPM and MS) were required for the induction and maturation of PSEs while induction and maturation of SSEs occurred on the MS medium only. Contrary to our finding, generally the same kind of media is found to be suitable for the induction of both primary as well as secondary somatic embryogenesis (Naing et al, 2013). It may be concluded that in A. lebbeck nutrient composition of WPM (low NH 4 + and NO 3 contents; high SO 4 2 concentration) is required for the onset of embryogenesis but long term maintenance of embryogenic competence was achieved with the use of MS formulations (higher concentrations of NH 4 + and NO 3 and low SO 4 2 content).…”
Section: Maturation and Secondary Somatic Embryogenesiscontrasting
confidence: 99%
See 1 more Smart Citation
“…Here it could be noticed that the two different media (WPM and MS) were required for the induction and maturation of PSEs while induction and maturation of SSEs occurred on the MS medium only. Contrary to our finding, generally the same kind of media is found to be suitable for the induction of both primary as well as secondary somatic embryogenesis (Naing et al, 2013). It may be concluded that in A. lebbeck nutrient composition of WPM (low NH 4 + and NO 3 contents; high SO 4 2 concentration) is required for the onset of embryogenesis but long term maintenance of embryogenic competence was achieved with the use of MS formulations (higher concentrations of NH 4 + and NO 3 and low SO 4 2 content).…”
Section: Maturation and Secondary Somatic Embryogenesiscontrasting
confidence: 99%
“…Similar to our finding, Mithila et al (2003) reported somatic embryogenesis at higher TDZ doses. Naing et al (2013) also reported KN to be the best PGR for the enhancement in the number of somatic embryoids induction per explant followed by BA and TDZ. KN also proved to be highly efficient for callus proliferation and subsequent differentiation of embryoids from leaf explants of cumin (Tawfik and Noga, 2002).…”
Section: Primary Somatic Embryogenesismentioning
confidence: 92%
“…However, combination with IBA exhibited a reasonable number of somatic embryos (Table 3). Naing et al (2012) also reported that no formation of embryo from leaf explants of Chrysanthemum cv. Euro when cultured on the medium containing TDZ alone, but combination with 2,4-D produced secondary embryos growth.…”
Section: Anatomical Observationmentioning
confidence: 97%
“…This is possible by applying two methods: adventitious shoots [Broertjes et al 1976, Jerzy and Zalewska 1997, Song et al 2011, Teixeira da Silva et al 2015 and somatic embryogenesis [Lema-Rumińska and Śliwińska 2015]. These methods involve growth regulators; in addition, the regeneration often occurs indirectly via callus [Zalewska et al 2011, Xu et al 2012, Naing et al 2013a, b, Lema-Rumińska and Niedojadło 2014. As a consequence, the resulting plants can be unstable [Miler and Zalewska 2014].…”
Section: Introductionmentioning
confidence: 99%